(untitled) (London, 1979)
This book introduction and overview. World food and agriculture to the mid-1980. World food and agriculture to 2000. Sustainable growth in production...
Keywords: Nông nghiệp,Agriculture; Khía cạnh kinh tế,Dự báo,Economic aspects,Forecasting